The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1152/japplphysiol.00543.2016
|View full text |Cite
|
Sign up to set email alerts
|

Microscale distribution and dynamic surface tension of pulmonary surfactant normalize the recruitment of asymmetric bifurcating airways

Abstract: We investigate the influence of bifurcation geometry, asymmetry of daughter airways, surfactant distribution, and physicochemical properties on the uniformity of airway recruitment of asymmetric bifurcating airways. To do so, we developed microfluidic idealized in vitro models of bifurcating airways, through which we can independently evaluate the impact of carina location and daughter airway width and length. We explore the uniformity of recruitment and its relationship to the dynamic surface tension of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Airway closure exacerbates inhomogeneity of regional lung ventilation that is likely associated with ventilator-induced lung injury (VILI) (Bellani et al 2016). Yamaguchi et al demonstrated that the distribution and dynamic surface tension of pulmonary surfactant were important for enhancing the recruitment uniformity in an asymmetric airway bifurcation (Yamaguchi et al 2014;Yamaguchi et al 2017). Unfortunately, there have been few studies directed toward measurements of viscosity and surface tension of pulmonary fluids and its effect on PEEP and regional distribution of lung ventilation in ARDS.…”
Section: = 8 ⁄mentioning
confidence: 99%
“…Airway closure exacerbates inhomogeneity of regional lung ventilation that is likely associated with ventilator-induced lung injury (VILI) (Bellani et al 2016). Yamaguchi et al demonstrated that the distribution and dynamic surface tension of pulmonary surfactant were important for enhancing the recruitment uniformity in an asymmetric airway bifurcation (Yamaguchi et al 2014;Yamaguchi et al 2017). Unfortunately, there have been few studies directed toward measurements of viscosity and surface tension of pulmonary fluids and its effect on PEEP and regional distribution of lung ventilation in ARDS.…”
Section: = 8 ⁄mentioning
confidence: 99%
“…This parenchymal heterogeneity can drive further injury, however, higher mean airway pressures, a function of both pressure and time, also have a stabilizing effect on the parenchyma (Roy et al, 2013;Ryans et al, 2019). Yamaguchi et al (2017) demonstrated in an in vitro model of non-uniform bifurcating airways that flow will divert to the airways of lower resistance. Variation in airway width affects both hydraulic and capillary pressures and therefore has a greater divergence pattern as compared with variations in airway length, which affects hydraulic resistance alone (Yamaguchi et al, 2017).…”
Section: Alveolar Recruitment Over Timementioning
confidence: 99%
“…Yamaguchi et al (2017) demonstrated in an in vitro model of non-uniform bifurcating airways that flow will divert to the airways of lower resistance. Variation in airway width affects both hydraulic and capillary pressures and therefore has a greater divergence pattern as compared with variations in airway length, which affects hydraulic resistance alone (Yamaguchi et al, 2017). The study demonstrated that a 15% change in width between two airways can lead to a 100-fold change in relative velocity through the airways when combined with high surface tension, but that lower surface tension has a protective effect on asymmetric reopening (Yamaguchi et al, 2017).…”
Section: Alveolar Recruitment Over Timementioning
confidence: 99%